2022
DOI: 10.3393/ac.2020.00941.0134
|View full text |Cite
|
Sign up to set email alerts
|

Should transanal total mesorectal excision be implemented in medium-sized colorectal unit? technical and oncological outcome

Abstract: This study was performed to evaluate the outcome of implementation of transanal total mesorectal excision (TaTME) for low rectal cancer in a regional hospital and in comparison to laparoscopic (Lap) TME. Methods: Consecutive patients with low rectal cancer of which the lowest border of the tumour was located beween 1 and 5 cm from the puborectalis who underwent TME at North District Hospital between January 2013 and December 2019 were included. Clinical, operative, and pathologic outcomes were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The desirable prerequisites for a trainer for TaTME were at least 30 cases performed independently, provision of training courses with possible cadaveric resources and an academic output of at least 2 papers a year. This was validated in a recent paper by Ho et al [ 37 ], where they reported safe perioperative and oncological outcomes in their medium-sized colorectal unit of around 30 rectal cancer resections a year.…”
Section: Mounting the Curvesupporting
confidence: 57%
See 1 more Smart Citation
“…The desirable prerequisites for a trainer for TaTME were at least 30 cases performed independently, provision of training courses with possible cadaveric resources and an academic output of at least 2 papers a year. This was validated in a recent paper by Ho et al [ 37 ], where they reported safe perioperative and oncological outcomes in their medium-sized colorectal unit of around 30 rectal cancer resections a year.…”
Section: Mounting the Curvesupporting
confidence: 57%
“…The desirable prerequisites for a trainer for TaTME were at least 30 cases performed independently, provision of training courses with possible cadaveric resources and an academic output of at least 2 papers a year. This was validated in a recent paper by Ho et al [37], where they reported safe perioperative and oncological outcomes in their medium-sized colorectal unit of around 30 rectal cancer resections a year. Perhaps the most important is direct clinical proctorship with regular evaluation of pathological quality of resected TME specimens and analysis of clinical outcome data including complications, mortality, and oncological results.…”
Section: Mounting the Curvesupporting
confidence: 55%
“…There are studies on various approaches for organ preserving surgery. Representative surgical method is the trans-anal approach, which is to perform TME by approaching through the anus [ 92 93 98 99 ]. There are several studies showing that oncologic safe is obtained, and functional outcome is not inferior to laparoscopy [ 98 100 ].…”
Section: How To Improve Surgical Outcomesmentioning
confidence: 99%
“…There has been steady progress in the field of minimally invasive surgical treatments for colorectal cancer over the past decade [1][2][3][4][5][6][7][8]. Laparoscopic surgery has revolutionized the field of colorectal cancer treatment, gaining widespread acceptance and becoming a routine choice for many patients due to its feasibility and proven oncologic safety in numerous studies [1][2][3]5,7].…”
Section: Introductionmentioning
confidence: 99%